Concurrent measurement of sample and reference waveforms in an optical-pump terahertz-probe system using a controlled optical diaphragm shutter - Jessica Afalla; Hideaki Kitahara; Takeshi Moriyasu; Masahiko Tani (Journal of Physics and Its Applications, 2019)
We present concurrent measurement of sample and reference terahertz waveforms for an optical-pump terahertz-probe spectrometer, using a controlled optical diaphragm shutter for the optical pump line. When waveforms are taken consecutively, laser power fluctuations and other experimental conditions can introduce spectral artefacts, thus a concurrent measurement is preferred. Instead of techniques based on double modulation, the use of the diaphragm shutter eliminates the need for a second lock-in amplifier and/or constricted alignment due to the use of a single chopper blade for modulating two signals, simultaneously. Drude fitting of the complex conductivity obtained for GaAs confirms that measurements obtained using our set-up agree with reported scattering times.